2022
DOI: 10.24875/gamo.17000049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a protocol for the prevention and care of oral mucositis in pediatric patients diagnosed with cancer

Abstract: Introduction: Oral mucositis (OM) is a common complication associated with cancer treatment, and it can range from mild to severe degree. Up to 80% of children undergoing chemotherapy will experience some degree of OM, which can get to increase mortality by up to 40% in severe cases. Although OM incidence differs according to cancer type and treatment regimen, children with hematological malignancies experience higher incidence and prevalence than children diagnosed with solid tumors. According to the above, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…It is therefore important to implement preventive and therapeutic guidelines to maintain excellent oral health and reduce the risk of developing oral mucositis. Ávila-Sánchez et al [19] observed a lower prevalence of oral mucositis than that reported in the global literature after implementing a dental health protocol; the severity of oral mucositis was reduced within 7 days of implementing this protocol. Therefore, we also plan to introduce an oral health protocol at our institute to reduce the risk of oral mucositis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is therefore important to implement preventive and therapeutic guidelines to maintain excellent oral health and reduce the risk of developing oral mucositis. Ávila-Sánchez et al [19] observed a lower prevalence of oral mucositis than that reported in the global literature after implementing a dental health protocol; the severity of oral mucositis was reduced within 7 days of implementing this protocol. Therefore, we also plan to introduce an oral health protocol at our institute to reduce the risk of oral mucositis.…”
Section: Discussionmentioning
confidence: 93%
“…Oral health remains a public health concern in Mexico, including in Durango state where 50% of children have dental problems (especially caries); hence, it is possible that the development of oral mucositis is related to poor oral hygiene [19]. It is therefore important to implement preventive and therapeutic guidelines to maintain excellent oral health and reduce the risk of developing oral mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired function of the epithelial barrier may lead to secondary and systemic infections, which result in higher demands for wide-spectrum antibiotics [ 1 , 4 , 5 , 6 ]. Besides that, OM is often associated with cancer therapy interruptions or dose reductions, resulting in worsened clinical and economic outcomes and higher patient mortality [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to rapidly dividing cells, oral mucosa is highly sensitive to the damaging effects of cytotoxic drugs or radiotherapy (RT) to the head and neck region. Children and young adults are thus predisposed to develop this condition because they have a higher epithelial mitotic rate [ 5 , 7 , 8 ]. Age, as well as the type of malignancy and treatment regime, are some factors that influence the incidence of chemotherapy-induced OM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation